2010
DOI: 10.1177/1538574410363748
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Diabetes on Degree of Abdominal Aortic Aneurysm Tissue Inflammation

Abstract: Abdominal aortic aneurysm (AAA) progression and disease resistance are related to transmural degenerative processes and an inflammatory infiltration (INF). Diabetes is associated with low prevalence and growth rate of AAA. We sought to characterize INF in established AAA (INFAAA), in diabetic patients. From 89 male patients aged 52 to 83 years, aneurysm specimens obtained at open asymptomatic nonruptured AAA repair were graded for INF and immunostained using antibodies against T-lymphocytes (CD3) and macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
3
10
0
1
Order By: Relevance
“… 34–36 In contrast, a higher macrophage infiltration was observed in AAA wall of diabetic compared to non-diabetic patients who underwent AAA surgical repair and was correlated with serum glucose concentration. 79 AAA diameter was similar between diabetics and non-diabetics, and no significant difference was observed for T-lymphocyte infiltration. The discrepancy between those human and animal studies underlines the complex impact of diabetes on inflammation and suggests that the protective effect of DM on AAA development and progression may not be linked to its impact on inflammatory pathways ( Figure 1 ).…”
Section: Mechanistic Effects Of Diabetes On Aortic Aneurysmmentioning
confidence: 70%
“… 34–36 In contrast, a higher macrophage infiltration was observed in AAA wall of diabetic compared to non-diabetic patients who underwent AAA surgical repair and was correlated with serum glucose concentration. 79 AAA diameter was similar between diabetics and non-diabetics, and no significant difference was observed for T-lymphocyte infiltration. The discrepancy between those human and animal studies underlines the complex impact of diabetes on inflammation and suggests that the protective effect of DM on AAA development and progression may not be linked to its impact on inflammatory pathways ( Figure 1 ).…”
Section: Mechanistic Effects Of Diabetes On Aortic Aneurysmmentioning
confidence: 70%
“…Most of the studies published so far compared features between diabetic and non-diabetic patients with AAA ( 19 , 30 - 34 ). To the best of our knowledge, this is the first study addressing the association between insulin resistance and AAA.…”
Section: Discussionmentioning
confidence: 99%
“…32 DM is known to induce vascular inflammation in atherosclerotic tissues; 33,34 however, some studies also suggest that a similar phenomenon occurs among aneurysmal tissues which would seem inappropriate given the relationship between DM and AAA. 35 Indeed, Arapoglou et al 35 examined macrophage levels in patients undergoing open AAA repair and found significantly higher levels in aortic tissues from patients with DM compared to those without (p = 0.02) and a positive correlation with serum glucose levels (r = 0.21, p = 0.04).…”
Section: Inflammationmentioning
confidence: 99%